Reducción sa Bohol sa Dantaon 16 hanggang 19: Katangian at Anyo - Ferrer, Amelia S. (Philippine Social Sciences Review, 2010)
Spanish colonialism was anchored on the physical manifestation of its hegemonic power over Philippine society through the establishment of reducción. It necessitated the creation of small and scattered Filipino communities into compact villages, a spatial reorganization that followed the mark of urbanity as defined by the Spaniards. When Manila was made the colonial center after Miguel de Legazpi’s arrival in the archipelago, the process of transforming native Filipino’s social and physical landscape took form in Luzon, Visayas and parts of Mindanao. At the center of these “new” communities stood the Catholic Church often the only symbol of Spanish hegemony in areas far from Manila. The process of reducción was designed not only to delimit the physical extent of conversion but also to alter the people’s way of life. This paper focuses on the history of this colonial institution in the island of Bohol.